Knowledge Sharing Behavior Model of Polytechnic Lecturer - Kusumanto, RD; Salamah, Irma (International Journal of Science, Technology & Management, 2023)
Knowledge sharing is very important for lecturers in implementing the tri dharma of higher education. By sharing knowledge, it will create creative ideas and innovations for lecturers. This study aims to find out how the behavior of sharing knowledge of polytechnic lecturers. Research on the knowledge sharing behavior of polytechnic lecturers has never been carried out. The research sample was 200 lecturers at the first six polytechnics in Indonesia. The behavior of sharing knowledge is seen from three factors: knowledge donating, knowledge collecting, and technology. The data was processed using LISREL 8.80. The results of the research are the dominant dimension in supporting the sharing of lecturers' knowledge. Polytechnics lecturer also tend to collecting more knowledge than share knowledge. This can be due to the lack of motivation of lecturers to share and competition. For this reason, polytechnic university management needs efforts to improve the culture of knowledge sharing among lecturers.